An insight into graphene oxide associated fluorogenic sensing of glycodye–lectin interactions. Issue 32 (27th July 2015) - Ji, Ding-Kun; Zhang, Yue; He, Xiao-Peng; Chen, Guo-Rong
Abstract : Fluorogenic glycoligand–lectin interactions are determined to be associated with graphene oxide in a size dependent manner. Abstract : Recently, there has been increasing interest in the construction of graphene oxide (GO) based fluorogenic composite materials (FCMs) for the detection of ligand–protein recognitions, which modulate numerous physiological and pathological processes in nature. In the sensing systems developed, GO has been used as a platform to assemble, and thus quench the fluorescence of dye-labelled ligands for the fluorogenic (fluorescence off–on) detection of proteins through the competitive formation of ligand–protein complexes, disassembling the GO composite. Here we show that the size, structure and loading concentration of GO may largely impact the sensing performance of GO-based FCMs. We synthesized four glycodyes that incorporate diverse natural glycoligands (as recognition groups) coupled with fluorescent dyes (as both the graphene binding and signal reporting group) with different emission wavelengths for comparison with GOs with different sizes. We determined that with the increase of size, the quenching ability of GO for the glycodyes increased, whereas the GO with a moderate size showed the best sensing performance for lectins (proteins that recognize glycoligands). The plausible mechanism of action was proposed. This research suggests that judicious quality control of GO is crucial for the construction of GO-based FCMs as biosensors.